PEMANFAATAN DIGITAL SEBAGAI PUSAT INFORMASI DI DESA BANGUN MULYA - Prihandoyo, C.; Indriastuty, Nina; Iskandar, Amir; Maharani, Aliyah (Jurnal Abdi Masyarakat Ilmu Ekonomi (JAMIE), 2023)
Digital Information Center (DIC) is an entity that plays a central role in managing, storing, and providing access to various types of information in digital form. DIC plays an important role in this digital era, where the amount and variety of data continues to grow rapidly. PID's main role in collecting, managing and distributing digital information to users. The discussion covered various types of DIC such as digital libraries, electronic archives, and government information portals. We also highlight the challenges faced by DIC, including managing privacy, data security, and the importance of information disclosure. This research underlines that DIC not only facilitates access to information, but also plays an important role in forming a knowledge society in the digital era. Bangun Mulya Village is currently starting to implement a digital platform that contains social media information related to activities in the village. Keywords : Center, Information, Digital